Effects of Summer Cooling Strategies on Post-Summer Cow Welfare: Evaluating Lameness and Behavior - Ahamed , Abdeen Sharfan; Bah , Musa; Ahmad, Melad (Insights in Animal Science, 2024)
The study aimed to compare the effect of different summer cooling strategies on post-summer lameness prevalence and behavior in Holstein Friesian cows. Twenty-one milking cows were randomly subjected to three different cooling strategies including: 1) a traditional approach (TRD), where cows were continuously cooled using a sprinkler during the daytime; 2) a reduced cooling strategy (2CS), which involved two cooling sessions of one hour each; and 3) increased cooling sessions strategy (4CS), with four cooling sessions daily. Each cooling session lasted for 1 h with a 12 min cycle (3 min water on and 9 min off) with a sprinkler flow rate of 1.25 L/min. The cows' lameness scores, lying behavior, standing behavior, and step counts were assessed during the post-summer period. The results revealed that the 4CS group had lower lameness prevalence compared to the TRD and 2CS groups (p = 0.015). Furthermore, the TRD and 2CS groups exhibited higher lying times and lower standing times during post-summer (p < 0.05), potentially indicating lameness pain and discomfort. Additionally, the step counts were lowest in the TRD group, followed by the 2CS and 4CS groups (p < 0.001). In conclusion, the continuous sprinkling (TRD) as a cooling strategy during summer showed potential negative consequences on post-summer cow welfare. The study highlights the significant influence of cooling strategies on post-summer cow welfare, emphasizing the need for considering long-term effects beyond the summer season.
Keywords: dairy cows; summer cooling strategies; post-summer welfare; lameness